Biogeographical aspects of drosophilids (Diptera, Drosophilidae) of the Brazilian savanna - Chaves,Natália Barbi (2008)
Some species of drosophilids have been intensely studied, especially in the areas of genetics and molecular biology. However, little is known about their ecology and biogeography. Here, we revise the records of Drosophilidae species in the Cerrado domain, in order to organize the available information and to recognize patterns of geographic distribution and endemism. The 43 sampled sites in this domain reveal 100 species of drosophilids (10 of them exotic to the Neotropical region), distributed in eight genera. The collections were concentrated mainly in the States of Goiás (including the Federal District) and Minas Gerais. Serra do Cipó is the site with the highest richness of these insects. Of the 90 neotropical species found in the Cerrado, 77 also occur outside this domain, most of which are in the Atlantic Forest. Since extensive areas of this domain were poorly sampled for drosophilids and most studies used only baited traps to collect the flies, this absence of endemism should be carefully considered. It is recommended new inventories in poorly sampled regions, especially in the northeastern part of the domain. Also diversification of collection methods and improvement in the taxonomy of these flies are proposed. These directions should provide a significant increase in the list of species of drosophilids of the Cerrado; and thus, increase our knowledge about its biodiversity.